TEMPAT KETIGA KOTATUA JAKARTA SEBAGAI GERBANG INTEROGATIF TERHADAP KEMAJUAN KOTATUA - Ferel Putra; Tatang Hendra Pangestu (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Kotatua Jakarta is a very crowded place visited by many visitors from many diverse areas. Other than that, Kotatua is also a home for some people, a place where they build their lives. This makes Kotatua becomes a high diversity place. Therefore, it is necessary to make a third place that unites people from different backgrounds for the sake of good Indonesian society growth by providing an interrogative place where people can meet, socialize, and interrogate their own lives by seeing other people’s lives. In addition, the project also has another goal, which is to improve the quality of Kotatua as a tourism area by building an information center that is useful for visitors, as well a community center that is useful for tourism workers there. Kotatua Jakarta Interrogative Gate talks about interrogative space for human growth that focuses on the provision of spaces that trigger social interaction that results in interrogation between human beings so they can become more open minded, of course while conveying information on both Kotatua and Jakarta tourism and preserving and enhancing the economy of pre-existing communities, as a gate that is opened for everybody. Keywords:  diversity; interrogate; open minded AbstrakKotatua Jakarta merupakan tempat yang sangat ramai dikunjungi banyak pengunjung dari daerah yang beraneka ragam. Disamping itu Kotatua merupakan sebuah tempat yang juga memiliki penduduk asli dalam jumlah yang sedikit. Hal ini membuat Kotatua menjadi sebuah tempat yang memiliki tingkat keberagaman yang tinggi. Maka, perlu dibuatlah sebuah tempat ke-3 yang bersifat mempersatukan masyarakat yang memiliki latar belakang berbeda, agar terjadilah interogasi yang mendewasakan yang dapat menjadi cikal bakal pertumbuhan masyarakat Indonesia yang baik. Proyek ini juga memiliki tujuan lain untuk meningkatkan kualitas Kotatua sebagai kawasan turisme dengan membangun sebuah pusat informasi yang berguna bagi pengunjung, dan pusat komunitas yang berguna bagi para pekerja turisme disana. Gerbang Interogatif Kotatua Jakarta berbicara tentang ruang interogatif yang membuat manusia bertumbuh yang berfokus dalam pengadaan ruang-ruang yang memicu adanya interaksi sosial yang berujung pada interogasi antar manusia yang mendewasakan, tentunya sambil menyampaikan informasi turisme Kotatua maupun Jakarta pada umumnya, dan melestarikan serta meningkatkan ekonomi komunitas yang sudah ada sebelumnya.